META ANALYSIS: EFFECTIVENESS OF ELECTRONIC MEDICAL RECORD (EMR) ON THE QUALITY OF HEALTH SERVICES - Kurniawan, Hendra Dwi; Widiyanto, Aris; Putri , Santy Irene; Prisusanti, Retno Dewi (Journal of Health Policy and Management, 2024)
Background : Progress technology information make all affected areas _ experience change . One of impact progress technology and information in the area health that is exists record medical electronic . There is a record medical electronic is designed to improve communication between providers within and between organizations by automating the collection, use, and storage of patient information. Additionally, record medical electronics can facilitate guideline compliance and decision support in service health . There is a record medical electronic expected can increase quality service health care in the facility service health . Subjects and Methods : This research is a meta-analysis and systematic review study , with PICO Population = Hospitals that use an EMR system . Intervention = _ Electronic Medical Records ( EMR ) . Comparison = Without Electronic Medical Record ( EMR ) . Outcome = Quality of health services. The articles used in this research were obtained from several databases including PubMed, ScienceDirect, and Google Scholar. Keywords to find articles are: “EMR” OR “ effectiveness of EMR use” OR “ quality of health care” OR “ effectiveness of EMR” Results : A total of 10 articles reviewed in this meta-analysis study came from America, Arabia, London and Taipei. Studies show that EMR use improves the quality of health care ( aOR = 0.87 (95% CI, 0.79 - 0.95). Conclusion : Service health services that use Electronic Medical Records ( EMR ) are 0.87 times more effective in improving health services compared to with service health who do not use an Electrocik Medical Record ( EMR ) .   Keywords : EMR, Quality of health services, Electronic Medical Records